The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0218910
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol levels after cold exposure are independent of adrenocorticotropic hormone stimulation

Abstract: We previously showed that postmortem serum levels of adrenocorticotropic hormone (ACTH) were significantly higher in cases of hypothermia (cold exposure) than other causes of death. This study examined how the human hypothalamic-pituitary-adrenal axis, and specifically cortisol, responds to hypothermia. Human samples: Autopsies on 205 subjects (147 men and 58 women; age 15-98 years, median 60 years) were performed within 3 days of death. Cause of death was classified as either hypothermia (cold exposure, n = 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…Our previous studies have shown that asphyxia, a hypoxic condition does not induce any noticeable response in the blood cortisol level. We did find that exposure to cold induces a response in blood cortisol levels [50]. In this study blood cortisol levels did not differ markedly between the different causes of death.…”
Section: Discussioncontrasting
confidence: 42%
“…Our previous studies have shown that asphyxia, a hypoxic condition does not induce any noticeable response in the blood cortisol level. We did find that exposure to cold induces a response in blood cortisol levels [50]. In this study blood cortisol levels did not differ markedly between the different causes of death.…”
Section: Discussioncontrasting
confidence: 42%
“…Cell lines culture AtT20: This mouse ACTH-secreting pituitary adenoma cell line was chosen to carry out our research because they are of pituitary origin and can modulate the release of ACTH upon stimulation with CRH. AtT20 cells are widely used for assessing the effects of different stimulus on cell renewal, viability and ACTH secretion (22)(23)(24)(25)(26)(27)(28). These cells lack functional D2 receptors (29,30).…”
Section: Accepted Articlementioning
confidence: 99%
“…The disparity between the current findings and those previously reported is likely due to the exposure duration. The acute rise of cortisol immediately following submersion that has been previously reported may have occurred in the current effort; however, as duration of submersion and cold exposure persisted, negative feedback inhibition of continued cortisol secretion likely attenuated the response (De Kloet et al, 1998;Shida et al, 2020)-except in individuals under perceived physiological stress. The inverse relationship between CORT and foot temperature indicated a heightened stress response in individuals nearing dive termination criteria of skin temperatures of 10 °C.…”
Section: Discussionmentioning
confidence: 58%